Multi Carrier based Multilevel Inverter with Minimal Harmonic Distortion - V.Jamuna Venkatesan; Gayathrimonicka Subarnan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents performance features of Asymmetric Cascaded Multilevel inverter. Multilevel inverters are commonly modulated by using multicarrier pulse width modulation (MCPWM) techniques such as phase-shifted multicarrier modulation and level-shifted multicarrier modulation. Amongst these level-shifted multicarrier modulations technique produces the best harmonic performance. This work studies about multilevel inverter with unequal DC sources using level shifting MCPWM technique. The Performances indices like Total Harmonic Distortion (THD), reduction of switches and number of DC Sources are considered. A procedure to achieve the appropriate level shifting is also presented is this paper.